Estimates of small Indian mongoose densities: Implications for rabies management. Issue 1 (4th October 2015) - Johnson, Shylo R.; Berentsen, Are R.; Ellis, Christine; Davis, Amy; Vercauteren, Kurt C.
ABSTRACT: The small Indian mongoose ( Herpestes auropunctatus ) is an invasive species and rabies reservoir in Puerto Rico. In the continental United States, terrestrial wildlife rabies is primarily managed by the National Rabies Management Program (NRMP) of the United States Department of Agriculture through oral rabies vaccination (ORV); the distribution of the vaccine baits is influenced by the population density of the target species. The NRMP uses a density index for estimating raccoon ( Procyon lotor ) population density to guide bait distribution. In Puerto Rico, a wildlife rabies vaccination program does not exist and vaccination of domestic animals is limited and not compulsory. To acquire information on density and other population dynamics, we compared a mongoose density index (MDI) adapted from the NRMP raccoon density index (RDI) to 3 other methods (2 types of capture–mark–recapture [CAPTURE and MARK] and spatially explicit capture–recapture [SECR]) for estimating density that incorporate modeling procedures on detection probabilities, and examined the spatial distribution of mongooses within our study plots. We used the RDI trapping protocol modified for mongooses to livetrap mongooses in El Yunque National Forest (El Yunque) and Cabo Rojo National Wildlife Refuge (Cabo Rojo) in fall of 2011 and spring of 2012 resulting in 4 trapping sessions. The MDI estimates were consistently less than those from other methods for estimating mongoose densities. The MDI detected a greater mongoose density during the wet season (0.55 mongooses/ha) than the dry season (0.34 mongooses/ha) at Cabo Rojo, consistent with all 3 other density estimation methods. Overall, the correlation coefficient between MDI and the other calculation methods was ≥0.68. When we examined known locations of mongooses and travel distances, we detected more mongooses in a smaller area within the study plot at Cabo Rojo than at El Yunque. The MDI provided information on the spatial distribution of mongooses, which will be needed to implement an ORV program to target mongooses in Puerto Rico. Published 2015. This article is a U.S. Government work and is in the public domain in the USA.